2020
DOI: 10.3389/fneur.2020.01028
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous Sclerosis Complex as Disease Model for Investigating mTOR-Related Gliopathy During Epileptogenesis

Abstract: Tuberous sclerosis complex (TSC) represents the prototypic monogenic disorder of the mammalian target of rapamycin (mTOR) pathway dysregulation. It provides the rational mechanistic basis of a direct link between gene mutation and brain pathology (structural and functional abnormalities) associated with a complex clinical phenotype including epilepsy, autism, and intellectual disability. So far, research conducted in TSC has been largely neuron-oriented. However, the neuropathological hallmarks of TSC and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 265 publications
(314 reference statements)
2
26
0
Order By: Relevance
“…Cell-specific mutations of TSC genes induced in both glia and neurons cause epilepsy in mice (44)(45)(46). Further, the neuropathological hallmarks of TSC include major morphological and functional changes in glial cells involving astrocytes, oligodendrocytes, NG2 glia, and microglia, as well as in neurons (47), and abnormal function of the mTOR pathway in glial cells is thought to contribute to seizures as well as cognitive co-morbidities in TSC as well as in TLE (48,49). Specimens surgically removed from people suffering from TLE show increased levels of pMTOR (S2448), pS6 (S235/236), and pS6 (S240/244) that are consistent with the activation of the mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-specific mutations of TSC genes induced in both glia and neurons cause epilepsy in mice (44)(45)(46). Further, the neuropathological hallmarks of TSC include major morphological and functional changes in glial cells involving astrocytes, oligodendrocytes, NG2 glia, and microglia, as well as in neurons (47), and abnormal function of the mTOR pathway in glial cells is thought to contribute to seizures as well as cognitive co-morbidities in TSC as well as in TLE (48,49). Specimens surgically removed from people suffering from TLE show increased levels of pMTOR (S2448), pS6 (S235/236), and pS6 (S240/244) that are consistent with the activation of the mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CSF1R is part of a family of receptors that are responsible for regulating microglial proliferation, survival, motility, and adhesion (14)(15)(16). As opposed to mTOR signaling, which is highly conserved across species and is ubiquitously found in numerous cell types (12), CSF1R is mainly expressed in microglia (14)(15)(16). In fact, mutations in this CSF1R receptor are associated with the loss of microglia and development of epilepsy in humans (17).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we found that inhibition of mTOR signaling with the drug rapamycin during SE-induced epileptogenesis suppressed microgliosis and attenuated the associated memory loss ( 8 ). While this evidence suggests that reactive microglial cells may be active participants underlying cognitive dysfunctions in SE and TLE, mTOR signaling cascade is expressed in neurons and astrocytes ( 12 ), thereby indicating that these other cell types may also play a role in this pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“… 2 While little is known on the impact that aberrant VEGFR-3 activation has in epilepsy, disruptions in cell-specific roles of mTOR signaling, such as those involved in the regulation of protein synthesis in dendrites, inflammatory/phagocytic properties in microglia, and glutamate transport mechanisms in astrocytes, can promote neuronal instability and hyperexcitability. 3 - 5 Consequently, mTOR hyperactivation has been linked to epileptogenesis and the generation of unprovoked seizures in both preclinical experimental models and drug-resistant epilepsies in humans. 3 - 5 Evidence that VEGFR-3 may be an upstream regulator of mTOR suggests that VEGFR-3/mTOR signaling may play a role in astrocytic-mediated epileptogenic processes.…”
Section: Commentarymentioning
confidence: 99%
“… 3 - 5 Consequently, mTOR hyperactivation has been linked to epileptogenesis and the generation of unprovoked seizures in both preclinical experimental models and drug-resistant epilepsies in humans. 3 - 5 Evidence that VEGFR-3 may be an upstream regulator of mTOR suggests that VEGFR-3/mTOR signaling may play a role in astrocytic-mediated epileptogenic processes. Thus, the study by Jeong et al interrogated whether VEGFR-3 signaling mediated mTOR activation as well as the dysregulation of glutamate transporter 1 (GLT-1) and reactive astrocytosis following pilocarpine-induced status epilepticus (SE) in mice.…”
Section: Commentarymentioning
confidence: 99%